PENERAPAN ASAS PEMBALIKAN BEBAN PEMBUKTIAN DALAM PENYELESAIAN SENGKETA KONSUMEN - Syam, Misnar (Departemen Hukum Perdata, 2018)
Consumer dispute related to violation of the consumer rights by businessman. Article 45 of Consumer Protection Law provides that the dispute may be settled by out of court dispute settlement or through litigation. In Indonesia, out of court dispute settlement of consumer disputes is conducted under the authority of Consumer Disputes Settlement Body (BPSK), while in litigation mechanism exercised with submission by the consumer personally, class action, or NGO claim. Consumer dispute settlement is part of civil litigation. According to Article 163 HIR/ 283 RBg, the party who alleges that he has a right shall proof his allegation. While, according to Article 19(5) of Consumer Protection Law, the businessman may be exempted from its duty, if it can proof that the damages suffered by the consumer is because of the consumer fault itself. Therefore, the businessman must prove that it did not commit any fault (shifting the burden of proof). The principle of shifting the burden of proof has adopted by Consumer Protection Law because the consumer has no sufï¬Â cient knowledge of materials, production process, and distribution process which done by the businessman regularly. The Consumer Protection Law has no clear provision on the implementation of shifting the burden of proof, while the same situation is also found in Supreme Court Regulation No. 1 of 2006 concerning Appeal on the Judgment of BPSK. Thus, there are inconsistency implementations on the shifting of the burden of proof between on case by case. It depends on the comprehension knowledge of the judges. Such situation may lead to ineffective implementation of Consumer Protection Law.